2008
DOI: 10.3168/jds.2007-0625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synchronization Protocols on Follicular Development and Estradiol and Progesterone Concentrations of Dairy Heifers

Abstract: The objectives were to evaluate the effect of synchronization protocols on follicular development and estradiol 17-beta (E(2)) and progesterone (P(4)) concentrations in dairy heifers. In experiment 1, 36 heifers were assigned to 1 of 6 synchronization protocols in a 3 x 2 factorial design: presynchronization with GnRH on study d -6 or -9 [study d 0 = initiation of the Cosynch + CIDR (controlled internal drug releasing insert containing P(4)) protocol] or no presynchronization (control) and one injection of PGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
(49 reference statements)
1
44
1
1
Order By: Relevance
“…In B. taurus beef cattle, Stevenson and Lamb (2016) reported little effect of P4 environment during development of the preovulatory follicle on pregnancy risk. Moreover, Holstein heifers that received PGF2α at the initiation of a Cosynch + CIDR protocol, and therefore, had lower circulating P4 during the protocol, resulting in larger ovulatory follicles, had similar P/AI as heifers not receiving PGF2α at the initiation of the protocol (Stevenson et al, 2008). In contrast, studies in B. indicus heifers or nonlactating cows indicated that high circulating P4 concentrations during synchronization of ovulation protocols reduced the growth of the dominant follicle, which negatively affected ovulation rate and pregnancy success (Carvalho et al, 2008;Dias et al, 2009;Peres et al, 2009).…”
Section: Corpus Luteum Function Luteolysis and Growth And Ovulationmentioning
confidence: 99%
“…In B. taurus beef cattle, Stevenson and Lamb (2016) reported little effect of P4 environment during development of the preovulatory follicle on pregnancy risk. Moreover, Holstein heifers that received PGF2α at the initiation of a Cosynch + CIDR protocol, and therefore, had lower circulating P4 during the protocol, resulting in larger ovulatory follicles, had similar P/AI as heifers not receiving PGF2α at the initiation of the protocol (Stevenson et al, 2008). In contrast, studies in B. indicus heifers or nonlactating cows indicated that high circulating P4 concentrations during synchronization of ovulation protocols reduced the growth of the dominant follicle, which negatively affected ovulation rate and pregnancy success (Carvalho et al, 2008;Dias et al, 2009;Peres et al, 2009).…”
Section: Corpus Luteum Function Luteolysis and Growth And Ovulationmentioning
confidence: 99%
“…Injection of PGF2α causes luteolysis of CL present and allows the cows to express estrus because of the reduced progesterone concentration (Stevenson et al, 2008). CONCLUSIONS It can be concluded that ovarian response after involving CIDR in the protocol for estrus synchronization especially using combination of GnRH and PGF2α were much effective to synchronize the initiation of estrus in dairy cows.…”
Section: Response Of Ovaries After Cidr or Without Cidr Based On Plasmentioning
confidence: 85%
“…This technique has widely been used as an important tool for increasing AI submission rate in beef and dairy herds (Macmillan and Peterson 1993;Xu and Burton 1999;Lucy et al, 2001). Otherwise, efficient and accurate detection of estrus are fundamental for successful reproductive management when no fixed-time AI protocols are implemented (Heersche and Nebel, 1994;Stevenson et al, 2008). This reproductive protocol, however, requires daily observation for signs of estrus and may result in extended interval from puberty to pregnancy depending on estrus detection efficiency and accuracy (Stevenson et al, 2008).…”
Section: Stage Of Estrus Cycle Prior To Estrus Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone devices are removed during PGF2α injection (day 7). Fixed-time artificial insemination is performed in 48, 56, or 60 hours after GnRH is injected [38][39][40]. Such protocols may be applied for 12-14 days with progesterone [41,42].…”
Section: Ovulation Synchronization Protocols + Progesteronementioning
confidence: 99%